Mood instability: Significance, definition and measurement. (October 2015) - Broome, M. R.; Saunders, K. E. A.; Harrison, P. J.; Marwaha, S.
Summary: Mood instability is common, and an important feature of several psychiatric disorders. We discuss the definition and measurement of mood instability, and review its prevalence, characteristics, neurobiological correlates and clinical implications. We suggest that mood instability has underappreciated transdiagnostic potential as an investigational and therapeutic target.